Prodromal Parkinsonism and neurodegenerative risk stratification in REM sleep behaviour disorder - Barber, T; Lawton, M; Rolinski, M; Evetts, S; Baig, F; Ruffmann, C; Gornall, A; Klein, J; Lo, C; Dennis, G; Bandmann, O; Quinnell, T; et al. (Oxford University Press, 2017)
Objectives. REM sleep behaviour disorder (RBD) is the most specific marker of prodromal alpha-synucleinopathies. We sought to delineate the baseline clinical characteristics of RBD and evaluate risk stratification models. Methods. Clinical assessments were performed in 171 RBD, 296 control and 119 untreated Parkinson’s (PD) subjects. Putative risk measures were assessed as predictors of prodromal neurodegeneration and Movement Disorders Society (MDS) criteria for prodromal PD were applied. Participants were screened for common LRRK2/GBA gene mutations. Results. Compared to controls, RBD subjects had higher rates of solvent exposure, head injury, smoking, obesity and antidepressant use. GBA mutations were more common in RBD, but no LRRK2 mutations were found. RBD subjects performed significantly worse than controls on UPDRS-III, timed ‘get-up-and-go’, Flamingo test, Sniffin Sticks and cognitive tests, and had worse measures of constipation, quality of life and orthostatic hypotension. For all these measures except UPDRS-III, RBD and PD subjects were equally impaired. Depression, anxiety and apathy were worse in RBD compared to PD subjects. Stratification of RBD patients according to antidepressant use, obesity and age altered the odds ratio of hyposmia compared to controls from 3.4 to 45.5. 74% (95% CI 66%, 80%) of RBD subjects met the MDS criteria for probable prodromal Parkinson’s compared to 0.3% (95% CI 0.009%, 2%) of controls. Conclusions. RBD subjects are impaired across a range of clinical measures consistent with prodromal PD and suggestive of a more severe non-motor subtype. Clinical risk stratification has the potential to select higher risk patients for neuroprotective interventions.